The Effectiveness of Metformin in Reducing the Risk of Preeclampsia in Patients with Polycystic Ovary Syndrome (PCOS) : A Systematic Review - Desi Dwi Nurchasanah; Lintang Dwi Marti (International Medical Journal Corp. Ltd, 2026)
Introduction: Polycystic Ovary Syndrome (PCOS) affects a significant proportion of women of reproductive age and is associated with an elevated risk of adverse pregnancy outcomes, including preeclampsia (PE). Metformin, an insulin sensitizer, has been proposed as a potential intervention to reduce this risk. However, the evidence regarding its effectiveness in preventing PE specifically in pregnant women with PCOS remains inconsistent. Methods: This study conducted a systematic synthesis of evidence from 41 sources, including major randomized controlled trials (RCTs) etc. The primary outcome was the incidence of preeclampsia. Secondary outcomes included early pregnancy loss, preterm delivery, gestational diabetes mellitus (GDM), and gestational weight gain. A methodological quality assessment was performed, distinguishing between evidence from RCTs and non-randomized studies. Results: The findings were discordant. Non-randomized studies reported a significant reduction in PE risk with metformin (e.g., Zheng et al., 2013: OR 0.53; Zhao & He, 2022: RR 0.61). However, analyses restricted to high-quality RCTs found no significant benefit. In the PregMet trial (Vanky et al., 2010), PE rates were 7.4% in the metformin group vs. 3.7% in the placebo group (p=0.18). The PregMet2 trial (Løvvik et al., 2019) also found no significant reduction. A meta-analysis of PCOS-specific RCTs (Nascimento et al., 2018) produced a pooled RR of 1.96 (0.81–4.77), trending toward harm. Conversely, consistent benefits were observed for secondary outcomes, including reduced early pregnancy loss, preterm delivery, and gestational weight gain. Discussion: The discrepancy between study designs highlights the risk of selection bias and confounding in non-randomized studies. Women who continue metformin throughout pregnancy may differ systematically from controls. While metformin improves metabolic parameters and reduces weight gain, the highest-quality evidence from placebo-controlled RCTs does not support its use for preeclampsia prevention in PCOS. The drug may reduce pregnancy-induced hypertension but not the specific pathophysiology of PE. Conclusion: Current high-level evidence does not support a clinically meaningful reduction in preeclampsia risk with metformin in pregnant women with PCOS. However, metformin is beneficial for reducing other maternal complications, such as preterm delivery and miscarriage. Future research should focus on specific high-risk PCOS phenotypes.